KAJIAN KANDUNGAN TIMBAL (Pb) DAN BAKTERI PELARUT FOSFAT PADA AREAL PERTANAMAN PADI DI KECAMATAN SUNGAI KAKAP KABUPATEN KUBU RAYA - Susana, Rini; Purwaningsih, Purwaningsih; Zulfita, Dwi; Warganda, Warganda; Nurjani, Nurjani (Agros Journal of Agriculture Science, 2023)
Immobilization of Pb in the form of bonds with inorganic compounds can occur with the availability of large amounts of solubilizing phosphate in the rhizosphere. High solubilizing phosphate in the rhizosphere can be an indication of the presence of phosphate solubilizing bacteria that work effectively in the rhizosphere. Exploration, isolation and characterization of these beneficial bacteria need to be carried out, so that strains that are able to grow well in rice growing areas can be propagated as biofertilizers. The purpose of this study was to examine the content of lead (Pb) and the characterization of phosphate solubilizing bacteria in rice planting areas in Sungai Kakap District, Kubu Raya Regency. This study used a field experiment method. Soil samples from the rice plant rhizosphere and rice plant samples were analyzed in the laboratory according to the variables that had been determined. The results of this study indicate that the available phosphate content in paddy fields in Sungai Kakap District ranges from 0.58 to 13.38 ppm. The paddy field in Sungai Rengas Village has a high available P content, while the paddy field in Sungai Kakap Village has a very low P status. The results of analysis of total Pb in the rice fields of Sungai Kakap District ranged from 11.55 to 18.71 ppm, the status of total Pb content was classified as low. The relationship between the availability of P in the soil and the levels of Pb is very low (r = -0.33), it is suspected that Pb does not affect the state of P in the soil due to the low concentration of Pb. The ability of bacterial isolates to dissolve phosphate in this study varied. Phosphate solubilizing bacterial isolates from rice roots had a greater ability to dissolve phosphate than isolates from paddy soil, both isolates from the rice fields of Sungai Rengas Village and Sungai Kakap Village.Keywords: Phosphate Solubilizing Bacteria, rice, paddy fields, lead.INTISARIImmobilisasi Pb dalam bentuk ikatan dengan senyawa anorganik dapat terjadi dengan tersedianya solubilizing fosfat dalam jumlah besar di rhizosfer. Solubilizing fosfat yang tinggi di rhizosfer dapat menjadi indikasi adanya bakteri pelarut fosfat yang bekerja effektif di rhizosfer. Eksplorasi, isolasi dan karakterisasi bakteri yang menguntungkan ini perlu dilakukan, agar strain-strain yang mampu tumbuh baik di areal pertanaman padi dapat diperbanyak sebagai biofertilizer. Tujuan penelitian ini adalah mengkaji kandungan timbal (Pb) dan karakterisasi bakteri pelarut fosfat pada areal pertanaman padi di Kecamatan Sungai Kakap Kabupaten Kubu Raya. Penelitian ini menggunakan metode eksperimen lapang. Sampel tanah dari rhizosfer tanaman padi dan sampel tanaman padi dianalisis di laboratorium sesuai dengan variabel-variabel yang telah ditentukan. Hasil penelitian ini menunjukkan kandungan fosfat tersedia pada lahan sawah di Kecamatan Sungai Kakap berkisar 0,58 – 13,38 ppm. Lahan   sawah Desa Sungai Rengas memiliki kandungan P tersedia dengan status tinggi, sedangkan lahan sawah di Desa Sungai Kakap status P tersedianya sangat rendah. Hasil analisis Pb total di lahan sawah Kecamatan Sungai Kakap berkisar 11,55- 18,71 ppm, status kandungan Pb total ini tergolong rendah. Hubungan antara ketersediaan P di dalam tanah dengan kadar Pb sangat rendah (r = - 0,33), diduga Pb tidak mempengaruhi keadaan P di dalam tanah karena konsentrasi Pb yang rendah. Kemampuan isolat bakteri dalam melarutkan fosfat pada penelitian ini berbeda-beda. Isolat bakteri pelarut fosfat yang berasal dari  akar padi mempunyai kemampuan melarutkan fosfat yang lebih besar dibandingkan isolat dari tanah sawah, baik isolat yang berasal dari sawah Desa Sungai Rengas maupun Desa Sungai Kakap. Kata Kunci: Bakteri Pelarut Fosfat, padi, sawah, timbal.